State-level estimates of the number of volunteer police in the United States - Dobrin, Adam (International journal of police science & management, 2017)
To effectively develop and evaluate policing policies and practices, researchers and stakeholders need to know the numbers of volunteer police officers. Limited national estimates exist in the United States, but have shortcomings. This study collects state-level counts of volunteer police from all 50 states (and the District of Columbia), and finds that relying on state-level counts of volunteer police officers is not an effective way of capturing this information. The implications are discussed and a solution is suggested.